Multidimensional well-being and income inequality in Central and Eastern Europe: A comparative analysis of CEE North and CEE Continental countries - Andrzej Geise; Małgorzata Szczepaniak (PLoS ONE, 2025)
Central Eastern European countries (CEEc) are characterized both by huge diversity in income inequality and, on average, by lower levels of well-being than in the other European Union (EU) countries. Given that income inequality may affect well-being negatively, the present study aims to explore the links between income inequalities and different dimensions of well-being in the eight CEEc, i.e. Poland, Czech Republic, Slovakia, Slovenia, Hungary, Latvia, Lithuania, and Estonia. The analysis is conducted in the two groups of CEEc regarding low and high inequality in income distribution, namely CEE Continental group and CEE North group (corresponding to post-socialist corporatist and post-socialist liberal, respectively). The multidimensional concept of well-being is applied, enabling deep exploration of its links with income inequalities in the following dimensions: subjective well-being (happiness) and objective well-being (material, health, educational, and environmental dimensions). We estimate the vector autoregression (VAR) models based on annual data disaggregated into quarterly data covering 2004 to 2020. The empirical results of Granger causality testing, which was used to investigate the links between income inequality and multidimensional well-being, indicated that not only are there differences between the groups in the studied patterns of interconnectedness, but also the groups of CEE North and CEE Continental countries are not homogeneous in those links.